DIGITAL TRANSFORMATION AND CYBER DISRUPTION IN THE OIL AND GAS INDUSTRY - Sayandeep Mandal , Abhijit Chirputkar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose: Digital transformation of Oil and Gas sector includes various types of technological changes in the industry and with these changes, various type of cyber threats also comes into the picture which is becoming a more serious concern for this industry. All the Industries are at the cusp of digital transformation, Oil and Gas sector is a very crucial sector, any potential damage by cyber threats will result in fall in market prices of oil severely. Research Gap: This sector is behind many other industries in terms of digital transformation and cybersecurity. Proper mapping of digitization of Upstream, Midstream and downstream services with its cyber vulnerabilities is required. Objective: The study focuses on the digital transformation and the cybersecurity of the Oil and Gas Industry. Research methodology: The research methodology for this research is qualitative research, the study has been done by taking consideration of various peer-reviewed literature in the area of digital transformation and cybersecurity in the oil and gas sector. Findings: After analyzing several research papers on cybersecurity, main cybersecurity threats have been identified and the framework has been proposed to mitigate the cyber risks